(untitled) (Scientific journal of the Fergana State University, 2024)
In recent years, the importance of advanced technologies and innovations in the development of the economy is increasing. The latest technologies can improve the efficiency of production and business processes. The so-called digital economy is a very broad topic in the formation of economic thinking of rural youth. There are many methods and strategies that can be applied to this problem. In order to encourage rural youth to participate in this field, the article mentions the need to improve their skills in programming, data analysis, and learning and teaching technological developments.